1992
DOI: 10.1210/jcem.75.5.1430077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing doses of recombinant human insulin-like growth factor-I on glucose, lipid, and leucine metabolism in man.

Abstract: The metabolic effects of recombinant human insulin-like growth factor-I (IGF-I) were assessed in five groups of normal male overnight-fasted volunteers receiving infusions of either 0, 5, 7.5, 15, or 30 micrograms/kg.h IGF-I during 8 h, resulting in total plasma IGF-I concentrations 127 +/- 7, 247 +/- 30, 389 +/- 39, 573 +/- 62, 620 +/- 105 ng/ml, respectively. Glucose consumption (euglycemic glucose clamp) increased dose dependently during IGF-I infusion (P < 0.001) up to 6.7 +/- 1.3 mg/kg. min in the 30 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
2

Year Published

1994
1994
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 32 publications
4
44
0
2
Order By: Relevance
“…In vitro and in vivo studies have shown that IGF-I is able to influence glucose, amino acid, and lipid metabolism (13)(14)(15), particularly by stimulating transport and utilization of glucose and amino acids and by promoting an overall positive protein balance through activation of protein synthesis and suppression of protein degradation (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that IGF-I is able to influence glucose, amino acid, and lipid metabolism (13)(14)(15), particularly by stimulating transport and utilization of glucose and amino acids and by promoting an overall positive protein balance through activation of protein synthesis and suppression of protein degradation (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the effects of IGF-I infusion on glucose and protein metabolism in healthy subjects (2,4,7,(19)(20)(21). These studies have demonstrated that although large doses of intravenous IGF-I have effects similar to insulin on glucose metabolism, the effects on protein metabolism are different and are characterized by reductions in circulating amino acid concentrations and whole-body protein flux (19), resulting in a direct stimulation of protein synthesis only when amino acid concentrations are maintained (2).…”
Section: Type 1 Diabetes Is Associated With Abnormalities Of the Growmentioning
confidence: 99%
“…Previous studies investigating the effects of IGF-I administration on NEFA metabolism have produced conflicting results, with decreased (19,20,41,42), increased, and unaltered (2,35) plasma NEFA levels reported by various investigators. It is likely that decreased GH-mediated lipolysis and simultaneously enhanced insulin sensitivity resulted in the lower circulating NEFA levels during the IGF-I administration.…”
mentioning
confidence: 99%
“…The differences between the groups were significant on days 2-6 (*P<0·001). Previous studies of IGF-I in non-traumatised animals and humans have shown that the peptide has a potent hypoglycaemic effect, despite a reducing effect on pancreatic islet -cell secretion (Boulware et al 1992, Mauras et al 1992, Turkajl et al 1992, Elahi et al 1993. In the present study a reduction in postoperative hyperglycaemia was seen in catabolic patients after major operation.…”
Section: Figure 1 Serum Concentrations Of Igf-i In Patients Given Igfmentioning
confidence: 99%
“…Supplementation with insulin-like growth factor-I (IGF-I), the proposed mediator of GH's somatotrophic actions in vivo, was recently shown to reduce nitrogen excretion after surgery and to improve nitrogen balance in healthy human volunteers (Clemmons et al 1992, Leinsköld et al 1995. Other studies in humans have demonstrated that IGF-I exerts insulin-like effects on glucose metabolism (Boulware et al 1992, Turkajl et al 1992. When administered at pharmacological doses, IGF-I reduces circulating insulin levels and exerts a hypoglycaemic effect (Guler et al 1987, Elahi et al 1993, Leinsköld et al 1995.…”
Section: Introductionmentioning
confidence: 99%